2021
DOI: 10.1007/jhep07(2021)039
|View full text |Cite
|
Sign up to set email alerts
|

Domain walls and CP violation with left right supersymmetry: implications for leptogenesis and electron EDM

Abstract: Low scale leptogenesis scenarios are difficult to verify due to our inability to relate the parameters involved in the early universe processes with the low energy or collider observables. Here we show that one can in principle relate the parameters giving rise to the transient CP violating phase involved in leptogenesis with those that can be deduced from the observation of electric dipole moment (EDM) of the electron. We work out the details of this in the context of the left right symmetric supersymmetric m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This requirement has been discussed in detail in [16][17][18][19]. It has also been shown that domain walls in SUSYLR can be successfully exploited for baryogenesis via leptogenesis while remaining consistent with low energy observables like the electric dipole moment of the electron, with a gravitational wave signature that can be detected in upcoming experiments [20]. More recent works like [21][22][23][24] have studied the gravitational wave consequences of bubble wall and/or domain wall collapse in LRSM, where the domain wall collapse is initiated by adding tiny explicit terms breaking the discrete leftright symmetry.…”
Section: Cosmology With Intermediate Scale Domain Wallsmentioning
confidence: 94%
“…This requirement has been discussed in detail in [16][17][18][19]. It has also been shown that domain walls in SUSYLR can be successfully exploited for baryogenesis via leptogenesis while remaining consistent with low energy observables like the electric dipole moment of the electron, with a gravitational wave signature that can be detected in upcoming experiments [20]. More recent works like [21][22][23][24] have studied the gravitational wave consequences of bubble wall and/or domain wall collapse in LRSM, where the domain wall collapse is initiated by adding tiny explicit terms breaking the discrete leftright symmetry.…”
Section: Cosmology With Intermediate Scale Domain Wallsmentioning
confidence: 94%